Meeting UK heat demands in zero emission renewable energy systems using storage and interconnectors. (15th January 2022) - Gallo Cassarino, Tiziano; Barrett, Mark
Highlights: Heat pumps require four times less electricity per unit of heat than green hydrogen. The heat cost of a green hydrogen-based system is double that of heat pumps. Increasing renewables by 33% or interconnections by 200% can halve UK energy storage. Abstract: Providing heat without emissions is a critical challenge to reach the 2050 UK net-zero target. Here, we simulate high renewable zero-emission energy system architectures with heat supply based on the major options of district heating, heat pumps, and electrolytic hydrogen boilers. We adopt a novel whole system modelling approach that combines meteorology-driven hourly simulations of demand and supply with storage, flexible technologies, and interconnections on the European scale. Our results show that systems with heat supply based on consumer or district heat pumps require about four times less electricity per unit of heat, with a heat cost about half of that from electrolytic hydrogen boilers. Furthermore, we compare trade-offs between investment in different infrastructure components. For example, we find that, compared to the reference scenario, increasing renewable capacity by 33%, or interconnections by 200%, can lower system storage capacity by up to 50%.